Stunting and Baby’s Milk: Evidence from Indonesia - Maulana, Muhammad; Herawati, Noknik Karliya; Wijaya, Miryam B Lilian (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2024)
Research Originality: This study uniquely examines the relationship between baby milk consumption and stunting rates in Indonesia using a two-stage least squares (2SLS) approach. It fills a gap in understanding why Indonesian consumers prefer sweetened condensed milk over baby formula, despite the increasing prevalence of stunting, offering new insights into the economic and educational factors influencing milk consumption.Research Objectives: To investigate the factors that influence baby milk consumption in Indonesia, such as milk prices, education levels, and population size. Also, to assess the impact of baby milk consumption on stunting rates among Indonesian children.Research Methods: The research uses an econometric approach, specifically two-stage least squares (2SLS) regression, analyzing data from 2005 to 2022.Empirical Results: The results indicate that baby milk consumption is significantly affected by milk prices, education levels, and population size. Interestingly, the study finds that higher consumption of baby milk is correlated with an increase in stunting rates.Implications: The findings suggest a need for greater parental awareness regarding the nutritional value of baby milk and potential policy interventions to regulate milk quality. Additionally, the results highlight the importance of educational campaigns to improve milk consumption behaviors and further research on the nutritional content of available baby milk products to address the stunting problem effectively.JEL Classification: D11, I15, O13, Q18, R22